IMPLEMENTATION OF HUMAN RIGHTS PRINCIPLES IN PATANI - Anton Minardi; Mohd Kamarulnizam Abdullah (PT. Media Akademik Publisher, 2025)
This research is describing what is the core crisis in Patani. Until the author came back from the location, there are happening of searching, capturing, imprisonment, tortures and killing. There are more than 2000 military Posts in this region. Military patrols and guards are often seen at several points. Even the passing cars were made by military personnel not by the police. There were several bomb explosions in several regions which indicate prolonged conflict. The research method used is qualitative with descriptive analysis. Direct data obtained from the source through interviews and direct discussions with Patani residents. They consisted of scholars, teachers, journalists, activists, women activists, youth, young women and lawyers. The results obtained that Patani was weakened after the 1909 treaty when several of its territories were devided between British and Siam. there are violations of human rights against thousands of people lasted today. While international institutions such as United Nations, Organization of Islamic Cooperation and Association of South East Asean Nations (ASEAN) seemed not interested in participating in completing this humanitarian tragedy. There was a wide desire to be independent from them even though there were also those under the pressure of the regime who wanted autonomy.